Validation of vertebral metrics: a mechanical instrument to evaluate posture of the spinal column - Quaresma, Cláudia (2013)
The purpose of this study is to verify the validity of the instrument Vertebral Metrics, designed to identify X, Y, and Z positions of - each vertebral apophyses, by comparing the results obtained from this instrument with those from an optoelectronic system of Stereophogrammetry, composed of 10 infrared cameras with a sampling frequency of 200 Hz. Methodology: The sample consisted of 11 women aged between 14 and 39 years. After marking the various points in the spinal column, from the 1st cervical vertebra to the 1st sacral vertebra, each woman's backbone was first measured with Vertebral Metrics and then measured with the optoelectronics system. Later, the results obtained with the two instruments were compared. Results: For our analysis we used an ANOVA model with 3 factors (Instrument, Subject and vertebrates) for the intervertebral distance.